Finite element analysis of steel frame high rise using ANSYS - Yap, Kai Xiang (2018)
This research deals with the analysis of a high rise frame by using both manual calculation and ANSYS program with the probabilistic method. By using this analysis, behaviors of the structure, such as stress, strain, deflection and deformation can be determined. The structure will then be checked according to Eurocode 3 to determine whether its behaviors pass all the code checking. Portal frame is commonly used for industrial building, but not for residential building. Thus, an existing reinforced concrete portal frame was used as the basis for the steel portal frame modeling and analysis. Due to the better quality of steel and low overall constructing cost, steel with 500 N/mm2 of yield strength was chosen for the portal frame analysis. Throughout the analysis, the materials and geometry used for the structure were satisfied for this research since it passed all the code checking. From the results obtained from simulation process, we able to know the real behaviors of the structure under random input parameters. Besides, results of cumulative distribution function, histogram plot, sensitivity plot and sample history plot by 10000 times of simulation were obtained through probabilistic analysis.